The Strong Influence of Pancasila Values in Indonesia in the Moral Shift Against the Paradigm of Science and Technology Development in the Era of the Industrial Revolution 4.0 - M Ichsan Syirait Ramadhan; I Gede Sumertha; Eri R Hidayat; Pujo Widodo; Herlina JR Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Shifts in morals or human behavior are inseparable from the paradigm of the development of science and technology, especially in the 4.0 revolution era. Various countries around the world are competing to continue to develop science and technology to be able to compete with various countries and complement the interests of their respective countries. However, over time, developments that should lead to positive things have become negatively biased as a result of being used by a handful of people to fulfill their personal or group interests. Cases of fraud, bullying, spreading fake news, etc, that utilize technology also cause a moral shift to occur. Indonesia, as a country that has a diversity of ethnicity, language, and customs is very vulnerable to being consumed by this. The presence of Pancasila as the ideology of the Indonesian nation can to filter all possibilities that occur as a result of the paradigm of scientific and technological development. Pancasila is formulated by various opinions from different backgrounds. So that Pancasila is considered as a unifier and glue of the diversity of Indonesian society. In addition, Pancasila is also used as a guideline and way of life for the nation both in formulating law and other rules, so that Pancasila is considered a national ideology that will not be eroded by the paradigm of the development of both science and technology.